2016
DOI: 10.1136/jech-2016-208086
|View full text |Cite
|
Sign up to set email alerts
|

Is being in paid work beyond state pension age beneficial for health? Evidence from England using a life-course approach

Abstract: BackgroundGiven the current policy emphasis in many Western societies on extending working lives, we investigated the health effects of being in paid work beyond state pension age (SPA). Until now, work has largely focused on the health of those who exit the labour force early.MethodsOur data come from waves 2–4 of the English Longitudinal Study of Ageing, including the life history interview at wave 3. Using logistic and linear regression models, we assessed the longitudinal associations between being in paid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 38 publications
3
52
1
Order By: Relevance
“…Only a few studies have accounted for the healthy worker effect when assessing the health consequences of working past retirement age. These studies did not observe any health benefits 17 , 20 …”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Only a few studies have accounted for the healthy worker effect when assessing the health consequences of working past retirement age. These studies did not observe any health benefits 17 , 20 …”
Section: Introductionmentioning
confidence: 78%
“…as a full- or part-time employee or being self-employed), and 0 if not employed 20 . We included demographic information in the form of age and marital status, defining marital status as a binary variable of value 1 if married and 0 if not married (including those bereaved or divorced).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study explores the health impact of paid work beyond standard retirement age in England. Using three waves of the English Longitudinal Study of Ageing and controlling for baseline socio-economic characteristics as well as work and health history, Di Gessa et al [ 14 ] find no statistically significant health effect of working beyond state pension age. A recent Swedish study by Hagen [ 17 ] finds no effects on drug prescription, hospitalizations, and mortality after a reform that increased the age at which female local government workers were entitled to full pension benefits from 63 to 65.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over the past few years, an extensive amount of research was published about the impact on health of professional transitions in late career focusing both on different types of transition such as retirement, return to employment, bridge jobs, or care activities and on different type of health measurements. such as self‐reported health, physical exposure, quality of life, or depression .…”
Section: Introductionmentioning
confidence: 99%
“…The topic remains controversial as the association between health and labor market participation is affected by different factors, such as the sector of activity, level of education, financial wealth, gender, the size of the company and the socio‐economic status . For instance, looking at longitudinal data from Sweden, Lindwall et al have pointed out that more positive changes in psychological health are observed for respondents who retired compared with those still working.…”
Section: Introductionmentioning
confidence: 99%